Analysis of Administrative Decisions of Foreign Regulatory Authorities - Information relevant (Безопасность и риск фармакотерапии)
Analysis of administrative decisions of foreign regulatory authorities on the limitation of circulation of medicines and/or the need for changes in the instructions for their medical use due to changes in the safety profi le, conducted by experts of the Scientifi c Centre for Expert Evaluation of Medicinal Products revealed 27 administrative decisions of foreign regulatory authorities. These decisions contained information on the following medicines registered in Russia: sartans (irbesartan, candesartan, losartan, olmesartan), hydrochlorothiazide, dimethylfumarate, human normal immunoglobulin, omalizumab, tacrolimus, terifl unomide, tofacitinib, ustekinumab, fi ngolimod, everolimus, atezolizumab, pembrolizumab, vinorelbine, daratumumab, imatinib, ipilimumab, lenalidomide, lenvatinib, methotrexate and ramucirumab.